Novos repertórios verbais em crianças pequenas: ouvinte, falante e classes de estímulos equivalentes - Almeida, Christiana Gonçalves Meira de (2014)
Research on stimulus class formation in very young children can bring important contributions to our current understanding of relations between verbal operants and concept formation repertoire. The present research was composed of two studies. The first one had four experiments that investigated stimulus class formations with spoken word, dissimilar objects and objects with common features. The second one described relationship between toddlers spontaneous vocalizations and theirs performances during conditional discrimination tasks. Participants were 14 children aged 18 to 27 months were participants. Auditory-visual conditional discriminations were taught, stimulus equivalence class formation and generalization performances were tested. The training and testing consisted of matching to sample procedures (MTS). The samples were spoken words, tridimensional objects or stickers. The comparison stimuli were tridimensional objects or stickers. In training, correct responses were followed by access to the object, praise and stickers. Incorrect responses were followed by a blank page. The minimum learning criterion was three correct responses out of four trials for each relation within eight trials. Testing was presented with or without reinforcement (depending on the experiment). Seven children learned baseline relations. Three of them reached the learning criteria in tests which suggested stimulus class formation. One child maintained stimulus equivalence performances in follow-up testing after 90 days. Study 2 analyzed videos recorded from three experiments of Study 1with six participants aged 22 to 24 months. The participants who showed higher frequency of vocalizations also achieved the equivalence tests criterion. The participants who did not emit any vocalizations during learning trials did not reach conditional relations learning criteria. It were found in the studies, results in favor and against the Naming Theory suggesting that under certain circumstances, repertoires of language and performance equivalence can coexist independently.